Physicochemical stability of compounded midazolam capsules over a one-year storage period - Boivin Pierre-Nicolas; Legendre Pauline; Bonnaure Anne-Claire; Lester Marie-Antoinette (De Gruyter, 2020)
In patients suffering from chronic liver disease, the hepatic metabolism of drugs is perturbed and the metabolic capacity is difficult to assess. Midazolam could be used as a phenotypical probe to predict the metabolic capacity of CYP3A to adjust dosages of drug substrates of this cytochrome. In this context, a prospective clinical trial is going to be conducted in our institution and a hospital preparation of midazolam capsules suitable for the clinical trial was developed. The objective of the present work was to assess the physicochemical stability of the formulation over 12 months to set shelf life.